19.9k views
2 votes
Please may I get help on this I will attach second image

Please may I get help on this I will attach second image-example-1
Please may I get help on this I will attach second image-example-1
Please may I get help on this I will attach second image-example-2
User Egg Vans
by
6.0k points

1 Answer

5 votes

option A

option A

option C

option B

option D

Step-by-step explanation:

Exponential growth function: f(t) = a(1 + r)^t

Exponential decay function: f(t) = a(1 - r)^t

a) y = (0.9)^t/2

when the number in the bracket of the exponential function is less than 1, it is a decay

0.9 < 1

1 - 0.9 = 0.1

We say, the function is an exponetial decay (option A)

b) y = (0.81)^t

The number in the bracket of the exponential function is less than 1, it is a decay

1- 0.81 = 0.09

0.81 < 1

We say, the function is an exponetial decay (option A)

c) y = (1.08)^(t +6)

y = (1 + 0.08)^(t +6)

1.08 > 1

Here, the number in the bracket is greater than 1. Hence, it is an exponential growth (option C)

d) y = (0.85)^t

The number in the bracket of the exponential function is less than 1, it is a decay.

1 - 0.85 = 0.15

0.85 = 1 - 0.15

Rewritting it: y = (1 - 0.15)^t

Where 0.15 = r.

The rate of decay of the function is 15% (option B)

e) y = (1/2)^t

The number in the bracket of the exponential function is less than 1, it is a decay.

1/2 < 1. Also, 1/2 = 0.5

1 - 0.5 = 0.5

Rewritting the function: y = (1 - 0.5)^t

where r = 0.5

The rate of decay of the function is 50% (option D)

User Shashi Penumarthy
by
6.8k points